The partnership study of Brahman cross in East Java - Syahriar Andinata; Budi Hartono; Umi Wisaptiningsih (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
This research aimed to know the revenue of beef cattle (Brahman cross) partnership system between feedlot companies and cattle farmers; observed the factors that affect the revenue from the sale of free-lactating cows and reared calves. Data collecting through the total sampling method by filling out questionnaires from 24 cattle farmers in four regions in East Java such as of Probolinggo Regency, Bojonegoro Regency, Batu City, and Malang Regency. The number of cattle (Brahman cross) raised is 155 pregnant heifers and 32 calves. The results showed that farmers suffered a loss from Probolinggo district with IDR 3,515.733, Bojonegoro Regency IDR 5,157,770, Malang Regency IDR 3,161,165 and Batu City amounted to IDR 2,247,017 in one period/animal Unit (AU). The factors that affect revenue were analyzed using multiple regression tests. The results showed that the factors such as the scale of ownership, number of family dependents, and production costs have a significant level (p value<0.05) that affect the revenue. The other factors like farmer age, education level, the experience of farming, and labor scale have no significant effect on the revenue of cattle farmers (p value>0.05).